Prototyping for UX designers : fundamentals, tools, and techniques - Inzucchi, Nick (Infinite Skills, 2015)
"In this Prototyping for UX Designers training course, expert author Nick Inzucchi will teach you how to design and evolve an iOS app from its initial mockup to a fully interactive prototype. This course is designed for the absolute beginner, meaning no previous prototyping experience is required. You will start by learning about designing for prototyping with Sketch, including how to create and transform, style, and draw. From there, Nick will teach you about click-through prototyping with InVision, including how to create projects and transitions, hotspot templates, and share and collaborate. Finally, you will learn about interactive prototyping with Framer, including using the Framer Studio interface, CoffeeScript, and animations. Once you have completed this computer based training course, you will be fully capable of using Sketch, InVision, and Framer to prototype your own apps."--Resource description page.